Study of The Efficiency of The Production Costs of Agricultural Resources for Tillage in Wet Rice Fields in The Village of North Pelawi District of Babalan Langkat - Ahmad Rizan Fadli; Saipul Bahri Daulay; Nazif Ichwan (Universitas Sumatera Utara, 2015)
One way to increase agricultural output in by agricultural intensification. One example of agricultural intensification is the use of appropriate processing resources. This study was aimed to assess the comparative efficiency of production costs and field capacity of processing time and processing resources of land use. Parameters measured were effective field capacity, the efficiency of tractors, fuel consumption, and economic analysis/processing fee. The results showed that the processing resources and processing time on wetland soil had significant effect on the effective field capacity and energy efficiency of the engine. Effective field capacity in the processing of land by human power in the morning was 0.056Ha/h and in the afternoon was 0.081Ha/h. Effective field capacity on the ground with the processing power of the engine in the morning was 0.787Ha/h and in the afternoon was 1,148Ha/h. The efficiency of the tractor in the morning was 61.357% with a fuel consumption was 1,041liters/hour. The efficiency of tractors in the afternoon was 89.492% with a fuel consumption was 1,338liters/hour. Processing costs for manpower resources in the morning and with afternoon was 2.000.000Rp/Ha and for the source of mechanical power in the morning was 882.300Rp/Ha and in the afternoon was 881.400 Rp/Ha. Keywords: effective field capacity, the cost of processing, wet rice.